PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL PADA MATERI POKOK KERUNTUHAN VOC UNTUK PESERTA DIDIK KELAS XI MIPA 4 SMAN 1 TUREN KABUPATEN MALANG - Ima Offiana; Dewa Agung Gede Agung; Ulfatun Nafi'ah (Universitas Negeri Malang, 2023)
The demands of contemporary era are increasingly complex and have impacte education field. Moreover, there are various advanced technologies are basically designed to make is easy for humans. Similary, in learning history, the use of technology can be used as a learning material tends to be complex and abstract often makes students unmotivated to learn history. Due to rationale, learning media are needed to concretize historical contentl so that students can easily understand and trigger the student’s imagination. Comic as a visual media with latest technology will be more easily accepted by students. It is because the learning media seems close to the reality of life of students as it is being subjected tailored to their needs. According to this, the purpose of research and developments is to produce and test the effectiveness of digital comic learning media on the subject matter of the collapse of VOC for students of class XI MIPA 4 SMAN 1 Turen Malang Regency. The method which has been used is a media program development model developed by Sadiman, et al. Furthermore, the results shows that the validity of the product obtained from material experts was 79.5% and from media experts amounted 98.9%. The results of product effectiveness and testing is small group which is conducted on 7 students obtained a percentage of 91.9%. Meanwhile, the results of trail us of large groups that were only attended by 28 students obtained a percentage of 91.1%. On the other hand, the result of the pre-test and post-test measurements increase in learning outcomes for students after using learning media. While the average pre-test score obtained was 42.6 and the average post-test score was 75.3. According to these data, it can’t be denied that the “VOC Collapse” digital comics learning media is classified exceptionally valid and completely effective to use in history learning.Tuntutan era kontemporer semakin kompleks dan berdampak pada bidang pendidikan. Apalagi ada berbagai teknologi canggih yang pada dasarnya didesain untuk memudahkan manusia. Begitu pula dalam pembelajaran sejarah, pemanfaatan teknologi sebagai bahan pembelajaran yang cenderung kompleks dan abstrak seringkali membuat siswa tidak termotivasi untuk belajar sejarah. Berdasarkan pemikiran tersebut, diperlukan media pembelajaran untuk mengkonkretkan isi sejarah agar siswa dapat dengan mudah memahami dan memicu imajinasi siswa. Komik sebagai media visual dengan teknologi terkini akan lebih mudah diterima oleh siswa. Hal ini karena media pembelajaran terkesan dekat dengan realitas kehidupan siswa karena disesuaikan dengan kebutuhannya. Berdasarkan hal tersebut maka tujuan penelitian dan pengembangan adalah untuk menghasilkan dan menguji keefektifan media pembelajaran komik digital pada materi pelajaran runtuhnya VOC untuk siswa kelas XI MIPA 4 SMAN 1 Turen Kabupaten Malang. Metode yang digunakan adalah model pengembangan program media yang dikembangkan oleh Sadiman, dkk. Selanjutnya hasil penelitian menunjukkan validitas produk yang diperoleh dari ahli materi sebesar 79.5% dan dari ahli media sebesar 98.9%. Hasil uji keefektifan produk dan uji coba kelompok kecil yang dilakukan pada 7 siswa diperoleh persentase 91.9%. Sedangkan hasil trail us kelompok besar yang hanya diikuti oleh 28 siswa diperoleh persentase sebesar 91.1%. Di sisi lain, hasil pengukuran pre-test dan post-test meningkatkan hasil belajar siswa setelah menggunakan media pembelajaran. Sedangkan rata-rata skor pretes yang diperoleh adalah 42.6 dan rata-rata skor postes adalah 75.3. Berdasarkan data tersebut, tidak dapat dipungkiri bahwa media pembelajaran komik digital “Keruntuhan VOC” tergolong sangat valid dan sangat efektif untuk digunakan dalam pembelajaran sejarah.